Medicines of the Earth and Traditional Cultures: Reflections on the Modes of Resistance and Construction of a Good Living - Oliveira, Jaqueline Rocha; Pereira, Maria Eliana Barbosa (Seven Editora, 2023)
This study discusses traditional medicine, understood here as practices of healing, care and knowledge rooted in the local culture. The debate on these practices permeates academic studies, public policies of the health system, and collective actions of social movements. One of the initiatives of collective actions in traditional medicine is present at Maju, the school of Traditional Cultures and Knowledge of the Earth. This school is located in Caratinga – mesoregion of the Doce River Valley of Minas Gerais – and has popular education as one of its main methodologies. The school's students are trained as therapists of traditional cultures, inspired by the worldview of good living, and by the meetings and work carried out with native peoples, quilombolas, healers, shamans, peasants and masters of local culture. These health care practices and the exchanges with the knowledge of the popular masters of the local culture are experienced by the students of the Maju school, and unfold in the realization of therapeutic work with social movements, especially the agroecological movement. The reflections raised in this essay are the result of research and studies on the subject in question, as well as the authors' experience report on the trajectories during the body therapy course that takes place at Maju, the school of Traditional Cultures and Knowledge of the Earth.DOI:https://doi.org/10.56238/innovhealthknow-036